Safety, tolerability and pharmacokinetics and pharmacodynamics of HL2351, a novel hybrid fc‐fused interleukin‐1 receptor antagonist, in healthy subjects: A first‐in‐human study - Oh, Jaeseong; Huh, Ki Young; Cho, Young‐Gyu; Cha, Ji‐Eun; Kim, Se‐Jin; Yoon, Seo Hyun; Park, Sung Sup; Yoon, Hyunyee; Lee, Jieon; Lee, Howard (British journal of clinical pharmacology, 2020)
Aims We performed a first‐in‐human study with HL2351, a novel hybrid Fc‐fused interleukin (IL)‐1 receptor antagonist, to evaluate its tolerability, pharmacokinetics and pharmacodynamics (PD) after a single subcutaneous (SC) administration in healthy subjects. Methods A randomized, double‐blind, placebo‐ and active‐controlled, dose‐escalation study was conducted. Eligible subjects randomly received a single SC administration of HL2351 (1, 2, 4, 8 and 12 mg/kg) or placebo in a ratio of 8:2. Subjects in the active‐controlled group received a single SC administration of anakinra at 100 mg. Serial blood samples were collected for pharmacokinetics and PD analyses. An ex‐vivo activation test was performed to evaluate the PD using peripheral blood mononuclear cells treated with IL‐1β. Anti‐HL2351 antibodies were determined at baseline and 29 days postdose. Tolerability was assessed throughout the study. Results HL2351 was eliminated more slowly than anakinra (terminal half‐life: 27.21–45.28 vs 3.97 h). Serum concentrations of HL2351 were increased dose‐proportionally. The mean apparent clearance of HL2351 were 0.6, 0.66, 0.75, 0.51, 0.65 L/h at 1, 2, 4, 8 and 12 mg/kg, respectively. The percent inhibition of IL‐6 expression varied widely (range: 0–92.1%), showing no clear trend or discernible difference between HL2351, anakinra and placebo. HL2351 was well tolerated after a single SC administration. Conclusion HL2351 was well tolerated and showed linear pharmacokinetic characteristics after a single SC administration at doses up to 12 mg/kg in healthy subjects. HL2351 remained in the body 7‐11 times longer than anakinra. HL2351 can be developed as a potential therapeutic alternative to anakinra.